Literature Review: Factors Associated with the Incidence of Chronic Energy Deficiency in Pregnant Women - Rahmawati Rahmawati; Adi Nugroho; Nia Kania (Indonesian Journal of Global Health Research, 2026)
Chronic Energy Deficiency in pregnant women is a serious health problem because it increases the risk of complications during pregnancy, childbirth, and fetal growth. Various studies have shown that the prevalence of chronic energy deficiency remains high and is influenced by multidimensional factors such as nutritional status, socioeconomic status, knowledge, and access to health services. The purpose of this study was to conduct a literature review to identify factors of chronic energy deficiency to strengthen evidence-based prevention strategies, specifically dietary patterns, maternal knowledge, and husband or family support. The study used a literature review by searching articles in PubMed, ScienceDirect, and Google Scholar. The inclusion criteria were articles published between 2021 and 2025, cross-sectional design, full papers, and discussing variables related to chronic energy deficiency in pregnant women. The MeSH (Medical Subject Heading)-based keywords were "Chronic Energy Deficiency" AND "Pregnant Women" AND "Food Consumption Patterns" OR "Husband/Family Support" OR "Mother's Knowledge". A total of 21 articles met the criteria and were analyzed. Most studies found a significant association between maternal knowledge and the incidence of chronic energy deficiency. Consumption patterns were also associated with the incidence of chronic energy deficiency, especially in mothers with low energy and protein intake. Husband or family support has been shown to be a reinforcing factor that helps mothers meet nutritional needs through emotional, informational, and financial support. Prevention of chronic energy deficiency requires a multidimensional approach that focuses on increasing nutritional knowledge, improving eating habits, and strengthening family support.